Effects of the background electrolyte on Th(IV) sorption to muscovite mica. (15th September 2015) - Schmidt, Moritz; Hellebrandt, Stefan; Knope, Karah E.; Lee, Sang Soo; Stubbs, Joanne E.; Eng, Peter J.; Soderholm, L.; Fenter, Paul
Abstract: The adsorption of tetravalent thorium on the muscovite mica (0 0 1) basal plane was studied by X-ray crystal truncation rod (CTR) and resonant anomalous X-ray reflectivity (RAXR) measurements and alpha spectrometry in the presence of perchlorate background electrolytes LiClO4, NaClO4, and KClO4 ([Th(IV)] = 0.1 mM, I = 0.1 M or 0.01 M, pH = 3.3 ± 0.3). RAXR data directly reveal a strong influence of the background electrolyte on the actinide sorption. No significant Th adsorption was observed in 0.1 M NaClO4, i.e., the Th coverage θ (Th), the number of Th per unit cell area of the muscovite surface (AUC = 46.72 Å 2 ), was ⩽0.01 Th/AUC, whereas limited uptake ( θ (Th) ∼ 0.04 Th/AUC ) was detected at a lower ionic strength ( I = 0.01 M). These results are in stark contrast to the behavior of Th in 0.1 M NaCl which showed a coverage of 0.4 Th/AUC (Schmidt et al., 2012a). Th uptake was also influenced by the electrolyte cation. Weak adsorption was observed in 0.1 M KClO4 ( θ (Th) ∼ 0.07 Th/AUC ) similar to the results in NaClO4 at lower ionic strength. In contrast, strong adsorption was found in 0.1 M LiClO4, with θ (Th) = 4.9 Th/AUC, a ∼10-fold increase compared with that previously reported in NaCl. These differences are confirmed independently by ex situ alpha spectrometry, which shows no measurable Th coverage in 0.1 M NaClO4 background in contrast to a large coverage of 1.6 Th/AUC in 0.1 M LiClO4 . Alpha spectrometry cannot be obtained in situ, but sample preparation requires several washing steps that may affect Th(IV) sorption, RAXR, however, is considered to reflect the in situ sorption structure. The CTR/RAXR analyses of Th-LiClO4 show the sorption structure consisting of Th species that are broadly distributed, centered at heights of 4.1 Å and 29 Å distance from the interface. Neither the very large distribution height of the second species nor the high coverage can be explained with (hydrated) ionic adsorption, suggesting that the enhanced uptake is presumably due to the formation and sorption of Th nanoparticles.